From the still to the tourist destination: challenges of the Pisco Route in Moquegua - Higueras Matos, Manuel Marco (2026)
This article analyzes the factors that limit the consolidation of the Pisco Route in Moquegua as an integrated tourism product, despite its winemaking tradition, heritage-valued wineries, and cultural recognition. Using a qualitative and interpretive approach with a territorial case-study design, 14 semi-structured interviews were conducted with producers, tour operators, association representatives, and public officials, complemented by on-site observation at wineries and documentary review. The findings show that pisco serves as an identity marker and cultural resource in gastronomic experiences; however, the route still functions as a set of dispersed visits rather than a planned circuit. The study concludes that the main bottleneck is not the absence of attractions but weak territorial governance: unclear rules, rotating leadership, and intermittent public-private agreements that hinder the standardization of services, signage, and promotion. The article proposes an explanatory model for emerging wine tourism destinations, in which institutional coordination capacity is decisive in transforming an available cultural resource into a competitive tourism product.